Sensitivity of walleye (Sander vitreus) and fathead minnow (Pimephales promelas) early-life stages to naphthenic acid fraction components extracted from fresh oil sands process-affected waters. (December 2015) - Marentette, Julie R.; Frank, Richard A.; Hewitt, L. Mark; Gillis, Patricia L.; Bartlett, Adrienne J.; Brunswick, Pamela; Shang, Dayue; Parrott, Joanne L.
Abstract: Unconventional oil production in Alberta's oil sands generates oil sands process-affected water (OSPW), which contains toxic constituents such as naphthenic acid fraction components (NAFCs). There have been few studies examining effects of NAFC exposure over long periods of early-life stage development in fish. Here we examined the effects of NAFCs extracted from OSPW to embryo-larval fathead minnow, exposed for 21 days. We compared the sensitivity of fathead minnow to walleye reared to 7 days post-hatch (18–20 days total). EC50s for hatch success, including deformities, and total survival were lower for walleye (10–11 mg/L) than fathead minnow (22–25 mg/L), with little post-hatch mortality observed in either species. NAFC exposure affected larval growth at concentrations below the EC50 in fathead minnow (total mass IC10 14–17 mg/L). These data contribute to an understanding of the developmental stages targeted by oil sands NAFCs, as well as their toxicity in a greater range of relevant taxa. Highlights: NAFCs from OSPW were more toxic to walleye embryos than fathead minnow. Little or no dose response in mortality was observed after hatch in either species. Fathead minnow larval growth was a more sensitive endpoint than hatch success. Chronic, large-volume early-life stage tests (21 days) improve estimates of NAFC toxicity. Abstract : Walleye embryos exposed to naphthenic acid fraction components were more sensitive than fathead minnow; embryos were more sensitive than larvae and exposure reduced larval growth.